2015
DOI: 10.3389/fnbeh.2015.00064
|View full text |Cite
|
Sign up to set email alerts
|

The alteration of gray matter volume and cognitive control in adolescents with internet gaming disorder

Abstract: Objective: Internet gaming disorder (IGD) has been investigated by many behavioral and neuroimaging studies, for it has became one of the main behavior disorders among adolescents. However, few studies focused on the relationship between alteration of gray matter volume (GMV) and cognitive control feature in IGD adolescents.Methods: Twenty-eight participants with IAD and twenty-eight healthy age and gender matched controls participated in the study. Brain morphology of adolescents with IGD and healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 55 publications
7
75
0
Order By: Relevance
“…Voxel-based morphometric studies demonstrate decreased gray matter in persons with IGD relative to controls in the inferior frontal lobe [41][42][43], insula [41,42], cingulate [41,43,44], dorsolateral prefrontal cortex (DLPFC) [43], precuneus [41,44], supplement motor area [42][43][44], amygdala [45••], and occipital lobe [46]. These brain areas are involved in cognitive control, error processing, decision-making, and reward.…”
Section: Biological Basismentioning
confidence: 99%
“…Voxel-based morphometric studies demonstrate decreased gray matter in persons with IGD relative to controls in the inferior frontal lobe [41][42][43], insula [41,42], cingulate [41,43,44], dorsolateral prefrontal cortex (DLPFC) [43], precuneus [41,44], supplement motor area [42][43][44], amygdala [45••], and occipital lobe [46]. These brain areas are involved in cognitive control, error processing, decision-making, and reward.…”
Section: Biological Basismentioning
confidence: 99%
“…Wang et al. () also detected decreased GMV in the bilateral anterior cingulate cortex (ACC), precuneus, supplementary motor area (SMA), superior parietal cortex, left dorsal lateral prefrontal cortex (DLPFC), left insula, and bilateral cerebellum atrophy in IGD subjects compared with the healthy controls. Weng et al.…”
Section: Introductionmentioning
confidence: 95%
“…Lin, Dong, Wang, and Du (2015) determined that individuals with IGD showed lower gray matter density (GMD) in the bilateral inferior frontal gyrus, left cingulate gyrus, insula, right precuneus, and right hippocampus than the healthy controls. Wang et al (2015) also detected decreased GMV in the bilateral anterior cingulate cortex (ACC), precuneus, supplementary motor area (SMA), superior parietal cortex, left dorsal lateral prefrontal cortex (DLPFC), left insula, and bilateral cerebellum atrophy in IGD subjects compared with the healthy controls. Weng et al (2013) reported decreased GMV in IGD subjects in the right orbitofrontal cortex (OFC), bilateral insula, and right SMA.…”
Section: Introductionmentioning
confidence: 95%
“…One small study in internet addiction showed lower cortical thickness in the OFC [Hong et al, 2013], with another reporting lower volume in dorsolateral prefrontal cortex (DLPFC) [Yuan et al, 2011] and two studies suggesting lower ACC volumes [Yuan et al, 2011;Zhou et al, 2011]. Two small studies in internet gaming disorders reported decreased volumes in OFC [Weng et al, 2013;Yuan et al, 2013], and two larger studies reported smaller volumes in cingulate cortex [Lin et al, 2014;Wang et al, 2015] with single studies reporting decreases in DLPFC , inferior frontal [Lin et al, 2014], superior parietal and inferior parietal [Yuan et al, 2013] cortices. With respect to subcortical structures, one small study reported higher ventral striatal (VS) volumes in gambling disorder [Koehler et al, 2013] with no subcortical differences reported in the other studies.…”
Section: Introductionmentioning
confidence: 99%